Effect of Supplementation of a Cryopreservation Extender with Pectoliv30 on Post-Thawing Semen Quality Parameters in Rooster Species - Esther Díaz Ruiz; Juan Vicente Delgado Bermejo; José Manuel León Jurado; Francisco Javier Navas González; Ander Arando Arbulu; Juan Fernández-Bolaños Guzmán; Alejandra Bermúdez Oria; Antonio González Ariza (MDPI AG, 2024)
Sperm cryopreservation is a fundamental tool for the conservation of avian genetic resources; however, avian spermatozoa are susceptible to this process. To cope with the high production of reactive oxygen species (ROS), the addition of exogenous antioxidants is beneficial. Pectoliv30 is a substance derived from alperujo, and in this study, its effect was analyzed on seminal quality after its addition to the cryopreservation extender of roosters at different concentrations. For this purpose, 16 Utrerana breed roosters were used, and seminal collection was performed in six replicates, creating a pool for each working day with ejaculates of quality. After cryopreservation, one sample per treatment and replicate was thawed, and several seminal quality parameters were evaluated. Statistical analysis revealed numerous correlations between these variables, both positive and negative according to the correlation matrix obtained. Furthermore, the chi-squared automatic interaction detection (CHAID) decision tree (DT) reported significant differences in the hypo-osmotic swelling test (HOST) variable between groups. Moreover, results for this parameter were more desirable at high concentrations of Pectoliv30. The application of this substance extracted from the by-product alperujo as an antioxidant allows the improvement of the post-thawing seminal quality in roosters and facilitates optimization of the cryopreservation process as a way to improve the conservation programs of different endangered poultry breeds.